2018
DOI: 10.1016/j.enbuild.2017.09.100
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evaluation of thermal comfort, ventilation performance indices and exposure to airborne contaminant in an airborne infection isolation room equipped with a displacement air distribution system

Abstract: This study is focused in determine the convenience of the use of displacement ventilation strategy in airborne infection isolation rooms (AIIRs). Comfort of the occupants of the chamber, IAQ indices and the exposition of the health worker (HW) to the contaminants emitted by the confined patient (P) are considered in a typical AIIR set up with a hot radiant wall representing an external wall. Three air ventilation rates are tested to determine their influence in the studied variables. Results show that IAQ indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 56 publications
(90 reference statements)
3
47
0
Order By: Relevance
“…These studies highlight the influence of the relative position of the supply diffusers and exhausts on the flow dynamics and hence on the ventilation performance inside the room. An experimental research has been also carried out using a hospital room setup but using DV for a range of ventilation rates from 6 to 12 ACH [37], showing the potential of this ventilation strategy for these spaces if it is well designed, highlighting the high importance of the heat loads in air distribution for this case.…”
Section: /35mentioning
confidence: 99%
See 2 more Smart Citations
“…These studies highlight the influence of the relative position of the supply diffusers and exhausts on the flow dynamics and hence on the ventilation performance inside the room. An experimental research has been also carried out using a hospital room setup but using DV for a range of ventilation rates from 6 to 12 ACH [37], showing the potential of this ventilation strategy for these spaces if it is well designed, highlighting the high importance of the heat loads in air distribution for this case.…”
Section: /35mentioning
confidence: 99%
“…This study is carried out in an experimental chamber with a typical IHR configuration setup [37] within the HVAC (heating, ventilation and air-conditioning systems) laboratory at the University of Cordoba. The experimental setup can be seen at The nine points that register tracer gas concentration around the inhalation point of HW are distributed in three columns (1, 2 and 3) and three rows (H, M and L) in the same vertical plane.…”
Section: Test Room and Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…The exhaled jet from the source manikin penetrated a long distance along the exhaled direction. On the other hand, there are also other studies https://doi.org/10.1016/j.buildenv.2019.106197 Received 30 March 2019; Received in revised form 7 June 2019; Accepted 7 June 2019 which have indicated that DV is an effective ventilation system for air infection wards [6][7][8]. Li et al [6] examined the exposure risk for the co-occupant under displacement, mixing and underfloor ventilation by the numerical study.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was found that DV could provide better air quality when the droplet residuals are smaller than 5 μm and the co-occupant is located a certain distance from the source. Berlanga [7] et al demonstrated that the exhaled contaminant could go up with the plume of the source manikin successfully when the manikin that exhaled contaminant air was facing up. The suitability of DV for avoiding nosocomial infection is still controversial [9], what is clear is that DV is superior to other ventilation systems when the contaminant is emitted with positive buoyancy force or is combined to the thermal plume of a heat source.…”
Section: Introductionmentioning
confidence: 99%